2021
DOI: 10.1177/20494637211039252
|View full text |Cite
|
Sign up to set email alerts
|

Rapid design and implementation of a virtual pain management programme due to COVID-19: a quality improvement initiative

Abstract: Background: The COVID-19 pandemic interrupted the delivery of face-to-face pain services including pain management programmes in the United Kingdom with considerable negative impact on patients with chronic musculoskeletal pain. We aimed to develop and implement a remotely delivered pain management programme (PMP) using video-conferencing technology that contains all the core components of a full programme: the ‘virtual PMP’ (vPMP). By reporting on the process of this development, we endeavour to help address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…It should be noted that there were also significant contextual factors occurring during the COVID19 pandemic that may well have impacted upon outcomes, either as mediators or moderators of treatment effects. Whilst there is evidence that virtual formats can be effective therapeutic formats for the delivery of pain management programmes 1,18 and psychological therapy 27,28 further research would be required to understand the relative contribution of format and contextual factors to CFT-PM outcomes during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that there were also significant contextual factors occurring during the COVID19 pandemic that may well have impacted upon outcomes, either as mediators or moderators of treatment effects. Whilst there is evidence that virtual formats can be effective therapeutic formats for the delivery of pain management programmes 1,18 and psychological therapy 27,28 further research would be required to understand the relative contribution of format and contextual factors to CFT-PM outcomes during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological approaches to pain management have well-been established for over 50 years and the most recent Cochrane review 1 included 75 randomised control trials of cognitive behavioural therapy (CBT) for pain ( n = 9401). Williams et al (2020) 1 found small to moderate effects of CBT for chronic pain with the strongest effect for mood (mostly depression) then catastrophic thinking, disability and least of all for pain.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation explored the acceptability of a remotely delivered pain management programme that was designed and implemented due to the COVID-19 pandemic. 9 Overall, this evaluation found that there is a spectrum of acceptability regarding the vPMP. Although the objective of this study was not to determine the number of patients that would prefer a remote or an in-person programme, some patients indicated that they were completely satisfied with the vPMP, whereas most patients inferred that they would not choose a vPMP over an in-person programme.…”
Section: Discussionmentioning
confidence: 86%
“…Considerable effort went into rapidly developing alternatives and soon virtual options for assessment and treatment delivery were trialled. 13 , 14 Within this context, our service redeveloped a number of previous in-person PMPs for virtual delivery, which included high and low intensity virtual PMPs and a virtual neuromodulation PMP, among other options. These virtual programmes were designed to meet the needs of patients previously recommended our in-person residential, outpatient and neuromodulation PMPs, with the more intensive PMPs designed to support people with more severe or complex pain-related disability and/or distress than the lower intensity PMP.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Although functionalities such as ‘breakout rooms’ can enable treatment participants to share their thoughts and feelings, this may disrupt the natural flow of communication and engagement that happens during in-person treatments. Additionally, participants can experience screen fatigue, 13 limiting the length and number of virtual sessions.…”
Section: Introductionmentioning
confidence: 99%